Green Corporate Governance sebagai Solusi dalam Meningkatkan Pengelolaan Risiko Keuangan: Studi pada Kantor Kecamatan Muara Enim, Sumatera Selatan - Rakha Maulana Saputra (Ekonomi Keuangan Syariah dan Akuntansi Pajak, 2025)
Global economic uncertainty has significantly impacted financial management, including within governmental institutions such as sub-district offices. This study aims to analyze how green corporate governance can serve as a solution to improve financial risk management at the Muara Enim Sub-District Office in South Sumatra. The research applies a qualitative explanatory approach using meta-analysis and focus group discussion (FGD) techniques. The findings reveal that economic uncertainty triggers high financial risks that cannot be adequately addressed through conventional good governance practices. Green corporate governance, with its sustainability orientation and strategic use of natural resources, emerges as an alternative solution to mitigate financial risk. Environmentally conscious governance practices, such as investment diversification based on local potential and waste management, have proven effective in enhancing financial stability and supporting domestic economic growth. This study recommends the implementation of green corporate governance as a policy approach that is adaptive to economic uncertainty and financial risk at the local government level.